(untitled) (Journal of the College of Basic Education, 2024)
The study aims at “the role of the non-verbal communication skills in the process of Teaching History in the primary schools from the teachers’ point of view”. An analytical descriptive approach was adopted, the sample was 90 male and female teachers; about 81.82% of the teaching community. A statistic consisting of 30 articles was distributed, addressing three points (students response to teaching history, class interaction and class discipline). After conducting several statistics the study concluded that the non-verbal communication skills highly contribute to the response of the learners of History in primary school to teaching, to achieve class discipline and to create a successful teaching experience In conclusion, the study recommended to prepare history teachers ,enable them to employ these skills in the best way possible to teach history, introduce them to the importance of gestures in providing knowledge and urge them to use the non-verbal rather than the verbal communication skills in order to safe time and to avoid distracting the class from its main goal which is History